To Study the Role of The Effect of Peroperative Tranexamic Acid on Blood Loss in Major Surgeries Around Hip - A Prospective Study (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Blood conservation plays a very important role in the care of a patient with lower extremity joint replacement and other surgeries. The procedure mandates consideration as major orthopaedic surgeries are associated with significant amount of blood loss both during and after surgery. Tranexamic acid (TA), a drug used to reduce perioperative blood loss, has been touted as a valuable adjunct to many perioperative blood conservation protocols. Aim and Objective: To find out the significance of Tranexamic acid in minimizing the peroperative and postoperative blood loss in major surgeries around hip and to compare the blood loss calculated by conventional method with mean of preoperative and postoperative haemoglobin levels. Material and Method: This study includes 40 patients all above 18 years of age operated for open reduction & internal fixation and fracture around hip and hip replacement surgeries such dynamic hip screw, proximal femoral nailing, total hip arthroplasty, hemiarthroplasty. Group A consist of 20 patients in which tranexamic acid was given and group B consist of 20 patients in which tranexamic acid was not given. Peroperative tranexamic acid was given and blood loss was measured by number of mops soaked, suction and drain collection and postoperatively haemoglobin levels were compared with preoperative haemoglobin levels and blood loss was measured in both the groups.Result: In the present study of 40 cases, the role of tranexamic acid in group A had significantly less blood loss as compared to group B.